EXPO, an exocyst-positive organelle distinct from multivesicular endosomes and autophagosomes, mediates cytosol to cell wall exocytosis in Arabidopsis and tobacco cells - Wang, Juan; Hillmer, Stefan; Robinson, David G. (The plant cell, 2011)
The exocyst protein complex mediates vesicle fusion with the plasma membrane. By expressing an (X)FP-tagged Arabidopsis thaliana homolog of the exocyst protein Exo70 in suspension-cultured Arabidopsis and tobacco (Nicotiana tabacum) BY-2 cells, and using antibodies specific for Exo70, we detected a compartment, which we term EXPO (for exocyst positive organelles). Standard markers for the Golgi apparatus, the trans-Golgi network/early endosome, and the multivesicular body/late endosome in plants do not colocalize with EXPO. Inhibitors of the secretory and endocytic pathways also do not affect EXPO. Exo70E2-(X)FP also locates to the plasma membrane (PM) as discrete punctae and is secreted outside of the cells. Immunogold labeling of sections cut from high-pressure frozen samples reveal EXPO to be spherical double membrane structures resembling autophagosomes. However, unlike autophagosomes, EXPOs are not induced by starvation and do not fuse with the lytic compartment or with endosomes. Instead, they fuse with the PM, releasing a single membrane vesicle into the cell wall. EXPOs are also found in other cell types, including root tips, root hair cells, and pollen grains. EXPOs therefore represent a form of unconventional secretion unique to plants.